2019
DOI: 10.1136/oemed-2019-106009
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and bullying behaviours at work among workers in Japan

Abstract: ObjectivesTo examine the relationship between adverse childhood experiences (ACEs), workplace bullying victimisation and bullying behaviours to subordinates among Japanese workers.MethodsWe conducted an internet-based cross-sectional survey among workers who had enacted 0, 1 and ≥2 types of bullying behaviours that had been directed towards subordinates in the past 3 years (n=309 for each group, total N=927). We assessed ACEs with questionnaires about adverse experiences at home and bullying victimisation at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…However, no studies have quantitatively examined whether adverse experiences in school are associated with the risk of Hikikomori. Furthermore, ACEs have been reported to increase the risk of employment problems (32,42) and workplace bullying (43), but no studies have investigated the association between ACEs and Hikikomori.…”
Section: Hikikomori or Social Withdrawalmentioning
confidence: 99%
“…However, no studies have quantitatively examined whether adverse experiences in school are associated with the risk of Hikikomori. Furthermore, ACEs have been reported to increase the risk of employment problems (32,42) and workplace bullying (43), but no studies have investigated the association between ACEs and Hikikomori.…”
Section: Hikikomori or Social Withdrawalmentioning
confidence: 99%
“…68 As for social relationship, Kizuki et al found that those with ACEs were 3.15 times more likely to display bullying behavior at work, suggesting that ACEs may have a significant impact on the development of attachment, which is crucial for establishing healthy social relationships. 69 Third, several ACEs, such as childhood poor well-being, poor academic performance, and low SES in adulthood were accumulated and shown to have dose-response toxic effects on the development of disease (cumulative model). Indeed, the concept of counting the number of ACEs can be considered as a cumulative model.…”
Section: Other Expanded Itemsmentioning
confidence: 99%
“…As for social relationship, Kizuki et al . found that those with ACEs were 3.15 times more likely to display bullying behavior at work, suggesting that ACEs may have a significant impact on the development of attachment, which is crucial for establishing healthy social relationships 69 …”
Section: Life‐course Epidemiology Perspectivementioning
confidence: 99%
“…Psihološki stres je sve što prijeti percepciji djeteta o sigurnom odnosu s odraslima jer će svaki poremećaj u odnosu uzrokovati oscilaciju i šok u unutarnjem miljeu 33 . Emocionalni i socijalni odnosi ostaju važan biološki utjecaj i nakon djetinjstva 34 ) zaključuju kako se to podcjenjivanje češće pojavljuje u muškaraca, a pogotovo od strane shizofrenih i psihijatrijskih pacijenata op-prevencija nasilja u obitelji i nepovoljnih dječjih iskustava na prvom mjestu kako bi se u budućnosti mogao prevenirati ili smanjiti rizik mobinga na poslu, kako za žrtve tako i za počinitelje nasilja koji nastaju upravo iz nepovoljnih dječjih iskustava 45 . Dobro je poznato da su zlostavljana djeca u puno većem riziku da sami budu zlostavljači od djece koja nisu zlostavljana.…”
Section: Nepovoljna Dječja Iskustva I Stresunclassified